2018
DOI: 10.3390/f9070441
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn from an Early Test on the Adaptation of Silver Fir Populations to Marginal Environments?

Abstract: In order to determine the adaptive potential of silver fir in the southeast of Poland, the stability of the height of its five-year-old progeny was analyzed. The study was conducted in two different population groups in a total of four environments, including one ecologically marginal environment. The linear mixed model was used to evaluate the differentiation of populations in terms of height growth. The genotype and genotype-by-environment interaction biplot (GGE) were used to verify the stability of height.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…This geographic area comprises two putative glacial refugia in southern Europe where silver fir survived during the last glaciation: in the Appenines and in the Balkan Peninsula of southeastern Europe. The remarkable growth performances and drought resilience of some provenances from the eastern distribution range (48,52,53) and southeastern (7,23,25,26) and southern edge (33) indicate that these populations, most of them peripheral, possess high adaptive potential, most likely as a consequence of the selection pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This geographic area comprises two putative glacial refugia in southern Europe where silver fir survived during the last glaciation: in the Appenines and in the Balkan Peninsula of southeastern Europe. The remarkable growth performances and drought resilience of some provenances from the eastern distribution range (48,52,53) and southeastern (7,23,25,26) and southern edge (33) indicate that these populations, most of them peripheral, possess high adaptive potential, most likely as a consequence of the selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other recent studies showed that European silver fir has high phenotypic plasticity [25] and is less vulnerable to drought stress than other conifers of temperate forests [26][27][28][29][30][31]. However, a possible decline may occur in the driest and warmest areas at the distribution edge [32][33][34]. Therefore, European silver fir could be one of the future species for consideration under changing climate conditions, particularly at lower altitudes in the mixed vegetation layer.…”
Section: Introductionmentioning
confidence: 99%
“…Because all individuals in a common garden share the same environment, any average difference in a trait between provenances of the same species has a genetic origin. The genetic variation in fitness-related traits is typically estimated in open pollinated progeny tests in common garden experiments, including the estimation of differentiation between provenances [5,6], and the study of this variation has its place in the field of quantitative genetics [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the climate-transfer-related constrains in studying provenance adaptability on common garden experiments, resulting from possible maladaptation of populations or diminishing effect of marginal site conditions (Klisz et al 2018(Klisz et al , 2019a, we applied multi-dimensional analysis of bioclimatic parameters. Two-object clusters (provenances 453 and 455), located closest to the provenance trial, would suggest a better adaptation of these two populations to the growing conditions than the provenances 390 and 451, which are climatically more distant.…”
Section: Climate-transfer Effectmentioning
confidence: 99%